Clinical, Demographic, and Socioeconomic Profile of Cleft Lip and Palate in Eastern India - Abhinav Raj Gupta; Rajiv Ahluwalia; Tina Chugh; Mrigank Shekhar Jha; Prem Vishva Natarajan (Journal of Pharmacy and Bioallied Sciences)
Aim: To determine the clinical, demographic, and socioeconomic profile of individuals with cleft lip and/or palate (CLP) at a high-volume center using data collected over 5 months in 2024. Materials and Methods: A prospective cohort observational case series was conducted within the cleft center departments of Orthodontics and Plastic Surgery at Santosh Dental College, Ghaziabad, Uttar Pradesh. The study examined age, sex, family history of clefts, socioeconomic status, and cleft types across various regions. A multidisciplinary approach, including orthodontic and dental treatments, speech therapy, and nutritional support, was used. The frequency and types of surgeries were evaluated at different age intervals: 0–5 years, >5–12 years, and >13 years. Secondary outcomes included parental literacy levels and pregnancy-related complications. Results: The study included 491 cleft patients with a mean age of 13.5 years. 45.41% belonged to the lower-middle class socioeconomic status, with a male-to-female ratio of 1.1:1. Bihar had the highest number of patients (204). Unilateral cleft lip and palate were predominant, especially among males. Common surgeries for 0–5 years were lip and hard palate closure, while older children underwent Secondary Alveolar Bone Grafting (SABG) and Rhinoplasty. 63% of patients actively participated in speech therapy, reflecting significant engagement with the interdisciplinary approach. Conclusion: This study provides foundational data on cleft patients treated at a high-volume center in Eastern India, highlighting the importance of a comprehensive multidisciplinary approach in managing CLP.